Gloucester Cathedral
The total effect of Gothic space, great windows are enriched carving has only remained in a few instances, of which Gloucester Cathedral choir is one. The detail of Christ in majesty, surrounded by angels, and all the glory of the Decorated period, is so far off the ground as to be almost unseen from the floor. Here is an entirely different use of sculpture from, say, the statuary of an Early English cathedral west front. The figures no longer tell a story, they have become a background to the space within which the story itself is performed. This ceiling is the culmination of a major rebuilding of the east end of the cathedral, which followed the setting up of a shrine to the murdered King Edward II. the Norman apse was replaced, and Norman work recased with stone mullions, which led directly to the adoption of perpendicular structures elsewhere.